PENGARUH PERILAKU KONSUMEN DAN LABEL HALAL PRODUK MAKANAN RUMAH TANGGA TERHADAP KEPUTUSAN KONSUMSI DI PALANGKA RAYA - Rahmaniar, Rahmaniar; Farid, Fuad; Herliani, Yeni (AL-QARDH, 2017)
Every individual has different manners for making choices, including choosing a need and desire. In the modern world of today has come a wide selection of products both local and international standards one of which is a food product. Namely food production in the country for food products imported from abroad, as well as processed food products such as cottage industries. Existing halal label on food products would have been very impact and influence for consumers, particularly Muslim consumers are encouraged to consume Thayyib food and halal. For this study will focus on the effect of consumer behavior and halal label food products by household to consumption decisions in Palangka Raya (Student Association of Islamic Economics at IAIN Palangka Raya) to determine the effect of consumer behavior and halal label food products by households to consumption decision analysis techniques Correlation Product Moment using SPSS 18.0.